Tuesday

March 31, 2015

March 31, 2015

Posted by **Shin** on Tuesday, May 21, 2013 at 10:50am.

- Math (Algebra) -
**Steve**, Tuesday, May 21, 2013 at 10:54amx^2-2x+m = (x-9)(x-n)

so,

-2 = -(n+9)

m = 9n

n = -7

m = -63

m+n = -70

- Math (Algebra) -
**Shin**, Tuesday, May 21, 2013 at 11:10amthanks a lot steve

**Answer this Question**

**Related Questions**

biology - Given the part of the molecule shown below, can the underlined atom ...

MATHS - The number 2+3√+5√−−−−−−...

Math (Algebra) - If a is a real number and a cubic equation f(x) = x^3 − ...

Trigonometry - Given the rectangular-form point (–1, 4), which of the following ...

calculus - Find an equation for the surface consisting of all points P(x, y, z) ...

Algebra - Use the quadratic formula to solve the equation. Give exact answers: ...

algebra - Hello, I need help answering a regents question. It is asking me to ...

Algebra - If a is a real number and a cubic equation f(x)=x^3−12x^2+(a+20)...

Algebra - Can you explain how to find the solution of 3x^2-2x+5, using the ...

add maths - Given that the quadratic equation is (2m+3)x^2+(4m-2)x-(m+1)=0.Find ...